Existence and Nonexistence of Periodic Solutions for a Class of Fourth-Order Partial Difference Equations - Dan Li; Yuhua Long (Journal of Mathematics)
In this paper, we investigate multiplicity, existence, and nonexistence of periodic solutions to a fourth-order partial difference equation via linking theorem and saddle point theorem. Our obtained results significantly generalize and improve some existing ones. We also provide examples and numerical simulations to illustrate applications of our main results.